Tests to determine the distribution of power in the shops of the Mechanical Engineering Department K.S.A.C. - Richards, Edward; Cowles, Edgar Andrew (My University, 1907)
Introduction: The object of these tests was to determine the distribution of power through the different shops of the mechanical engineering department. The line shafting of these shops is driven by means of electrical motors and the individual machines by belt drives. In order to determine the distribution, the output of the motors at different shop loads had to be obtained. For this purpose, two sets of tests were carried on. In the first set the relation between the input in the motors, or the electrical horse-power, and the output, or the brake horse -power, was determined. In this set of tests readings were taken of the voltmeter, ammeter, and of the scales simultaneously. A zero reading was taken while the motor was standing still. A certain weight was then placed on the scales and the prony brake was tightened till the scales balanced and two or three readings were taken about a half minute apart, at the close of every five minutes. An average of these readings was taken so as to avoid any error which might arise from just one reading. The weight on the scale beam was then increased about one pound and the procedure was repeated. This was continued till the motor was at its maximum test load.
Citation: Richards, Edward and Cowles, Edgar Andrew. Tests to determine the distribution of power in the shops of the Mechanical Engineering Department K.S.A.C.. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Power Distribution; Mechanical Engineering; Engineering at Kansas State University; Theses